(untitled) (KULT_online, 2014)
The anthologies Collision of Realities and Fremde Welten contain a selection of articles presented at the founding event of the Association for Research in the Fantastic (Gesellschaft für Fantastikforschung e.V., GFF) in Hamburg 2010. Research on the fantastic in literary texts and other media, the editors claim, has been established now in Europe as an academic standard. Both publications show the wide range possible in research that results from the GFF’s opting for an open definition of the ’fantastic.’